PENGARUH PENERAPAN METODE INDEX CARD MATCH TERHADAP HASIL BELAJAR PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH DASAR - Anjar Sari, Devi Shaaimin; Sabri, Tahmid; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to know the influence of Iindex card match method students’s learning outcome in learning Citizenship Education in class V of elementary school 28 Kubu Raya District,  this research used experimental method with Pre-Experimental Design research form one group pretest posttest design..The subject consisted of 20 in V grade.The technique of the data collection used was measurement technique.The data collection used was the form of  multiple choice  in the form of 50 questions. The result of the research was the average of post test result is 77,10. The result of t-test was 10,32 and ttable (α = 5% with db = 19) is 2.093 which means tcount (10.32)> ttable (2.093), so Ha was accepted. Conclusion there was the influence of Index Card Match method on student learning outcomes in grade V of elementary school 28 Kubu Raya Regency. Calculation of effect size (ES), got ES 0.94 (high category) Keywords:Citizenship Education, Index Card Match Method, Influence, Learning Outcome